Pendekatan Emotif dalam Cerpen Gulai Kam-Bhing dan Ibu Rapilus Karya Ahmad Tohari - Putri, Ratumas Aisyah; Rahmawati, Sophia; Wardani, Diah Octavia Kusuma (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
The purpose of this study is to identify and analyze the social values in these short stories, as well as to explain the role of emotions in reinforcing the moral message of literary works. The research method used in this analysis is a qualitative descriptive method, which is a comprehensive and in-depth study. The data collection technique involves reading and taking notes from the objects being studied. The short stories Gulai Kam-bhing and Ibu Rapilus by Ahmad Tohari contain many emotive meanings that can evoke emotions in readers. These emotions are grouped into three types, starting with negative emotions, namely: annoyed, confused, insulted, disappointed, anxious, surprised, troubled, regretful, tense, dislike, insensitive, and angry. Positive emotions include sincerity, admiration, laughter, nostalgia, kindness, and empathy. Lastly, neutral emotions include resignation. These emotions are evoked by the author's skillful narrative, and the words that carry emotional meaning include quickly, surprising, skinny, enjoyable, agility, aware, anxious, and so on.